Temporomandibular joint disorders due to edentulous spaces in young adults - Nasution, Aulia Nadhira Rayendra; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Acrylic resin artificial teeth are one of the components for dentures which are substitutes for natural teeth that have been lost and used to restore masticatory, speech, and aesthetic functions. Denture cleaning is necessary to avoid the colonization of microorganisms that can cause denture stomatitis. Natural denture cleaners are used as an alternative to minimize the effects of chemical denture cleaners that can affect the physical properties of acrylic resins such as surface roughness. 12.5% basil leaves extract was used as an alternative denture cleaning agent The purpose: To determine the effect on surface roughness value of acrylic resin artificial teeth immersed with 12.5% basil leaves extract. Methods: This research was an experimental laboratory. The samples used were 30 maxillary central incisor acrylic resin artificial teeth, combined with a square-shaped base measuring 20x20x6 mm, divided into 3 immersion groups: 10 in 12.5% basil leaves extract; 10 in alkaline peroxide; and 10 in aquabides. Measurement using a profilometer on the labial surface of artificial teeth. The results of the data were analyzed by One-way Anova. Results: The average surface roughness of acrylic resin artificial teeth after immersion in 12.5% basil leaves extract for 5 days was 0,246 ± 0,033 µm, alkaline peroxide 0,266 ± 0,016 µm, and aquabides 0,199 ± 0,020 µm with a value of p=0.0001(p<0.05). Conclusion:There is an effect of immersing acrylic resin artificial teeth in 12.5% basil leaves extract.KEY WORDS: teeth, artificial, resin, acrylic, extract, basil leaves, roughness.Pengaruh perendaman gigi artifisial resin akrilik dalam ekstrak daun kemangi terhadap kekasaran permukaanABSTRAKPendahuluan: Gigi artifisial resin akrilik merupakan salah satu komponen gigi tiruan sebagai pengganti gigi asli yang telah hilang dan digunakan untuk memulihkan fungsi pengunyahan, fungsi bicara, dan estetik. Pembersihan gigi tiruan diperlukan agar terhindar dari kolonisasi mikroorganisme yang dapat menyebabkan denture stomatitis. Bahan pembersih alami digunakan sebagai alternatif untuk meminimalkan efek yang ditimbulkan oleh pembersih gigi tiruan berbahan kimia yang dapat memengaruhi sifat fisik resin akrilik seperti kekasaran permukaan. Ekstrak daun kemangi 12,5% digunakan sebagai alternatif bahan pembersih gigi tiruan. Tujuan penelitian menganalisis pengaruh nilai kekasaran permukaan gigi artifisial resin akrilik yang direndam dengan ekstrak daun kemangi 12,5%. Metode: Jenis penelitian eksperimental laboratoris. Sampel yang digunakan adalah 30 gigi artifisial resin akrilik insisivus sentral rahang atas, disatukan dengan basis berbentuk persegi ukuran 20x20x6 mm, dibagi 3 kelompok perendaman yaitu perendaman dalam ekstrak daun kemangi 12,5%; alkalin peroksida; dan akuabides. Pengukuran menggunakan alat profilometer pada permukaan labial gigi artifisial. Hasil data dianalisis dengan uji One-way Anova. Hasil: Nilai rerata kekasaran permukaan gigi artifisial resin akrilik setelah direndam dalam ekstrak daun kemangi 12,5% selama 5 hari adalah 0,246 ± 0,033 µm, alkalin peroksida adalah 0,266 ± 0,016 µm, dan akuabides adalah 0,199 ± 0,020 µm dengan nilai p=0,0001(p<0,05). Simpulan: Ada pengaruh perendaman gigi artifisial resin akrilik dalam ekstrak daun kemangi 12,5% terhadap kekasaran permukaan.KATA KUNCI: gigi, artifisial, resin, akrilik, ekstrak, kemangi, warna.